(3TQM GdeJbfI (B( (3aj Yde GdaQGFV (B)s - (3CHi HcQ Hf CMeO GdSHJis; (3GHf GdeJbfI , CHh YHO Gddg eMeO Hf Ydj Hf eMeO Hf GdMSf GdQMHj,J (B577 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCRdi Hdi cjajI GdN s
(3BNQgG (B:s
(3Je GdTQM GdeHGQc HMeO Gddg hYhfg s
(3Gdajde ZjQ ehLhOs
(3hgh TQM Ydi CQLhRI CHj YHO Gddg Hf eMeO Hf GdMSjf GdQMHi GdeYQha HGHf GdeJbfI GdeJhai SfI (B577s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs